Preparation of PLA with High Impact‐Toughness and Reduced Internal Stress via Formation of Laminated, Bimodal Structure with Micro/Nanocells. Issue 11 (12th September 2021) - Xiang, Pei; Bi, Siwen; Mei, Fang; Deng, Chang; Yu, Dongdong; Chen, Xuhang; Yu, Peng
Abstract: The pressure‐induced‐flow (PIF) processing method is used to fabricate oriented, self‐toughening poly(lactic acid) (PIF‐PLA) with excellent mechanical properties. However, residual internal stress in PIF‐PLA may lead to their deformation and cracking. Hence, to eliminate internal stress, solid‐state supercritical carbon dioxide foaming (sc‐CO2 foaming) is applied to PIF‐PLA, with the resultant structure being called FOAM‐PLA. The microstructure and mechanical properties of the PLAs are characterized pre‐ and post‐foaming. Scanning electron microscopy results show PIF‐PLA to exhibit oriented texture structures composed of staggered microfibers. Following sc‐CO2 foaming, the PIF‐PLA is converted into a bimodal cellular structure consisting of micro and nano‐cells. According to the 2D wide‐angle X‐ray diffraction and Raman spectra results, this structure of the FOAM‐PLA can, through a marginal reduction of orientation, release significant amounts of internal stress. Moreover, the impact strength of FOAM‐PLA is found to be 32.7 kJ m −2, which is 10.2 times higher than that of crystalline PLA. This paper depicts the evolution of the PLA microstructure through the stages of PIF‐processing and the subsequent solid‐state sc‐CO2 foaming. Meanwhile, the mechanism of the internal stress reduction is promoted. Abstract : A novel strategy to prepare PLA with high impact‐toughness and reduced internal stress via formation of laminated, bimodal structure with micro/nanocells is presented. The combination of pressure‐induced‐flow processing with solid‐state supercritical CO2 foaming shows promise to optimize the performance of PLA. The evolution of the microstructure during processing and the mechanism of internal‐stress‐reduction in solid‐state CO2 foaming are proposed.